KNOWLEDGE OF BASIC PRODUCTION SAFETY STANDARDS AND RULES OF GOOD AGRICULTURAL PRACTICE IN OPINIONS OF AGRICULTURAL OWNERS - Płonka, Aleksandra R. (Acta Scientiarum Polonorum. Oeconomia, 2019)
The paper discusses the relation between issues related to environment protection and agricultural production carried out according to the adopted cultivation system. Surveys were conducted in 127 farms focused on plant production of which a fragment has been presented showing agricultural producers’ opinions about issues related to the Code of Good Agricultural Practice. One of underlying assumptions was an attempt to identify farmers’ attitudes to and their opinions about the practical application of principles adopted in the Code. The research shows that the application of the principles of good agricultural practice depended on the cultivation system adopted on the farm. Owners of farms managed in the integrated and organic production system fully declared knowledge of the Code itself and the content it contained, which translated into a higher level of their knowledge and implementation of recommendations in practice compared to people running traditional farms. One of major obstacles preventing the implementation of good agricultural practices by farms was the lack of information about the Code and promotion of its importance to the implementation of the concept of sustainable development.